Pembelajaran Berbasis Proyek Dalam Keterampilan Berbicara Siswa Kelas X MAN Kota Batu - Rahmayanti, Indah; Abidin, Munirul (Balai Diklat Keagamaan Surabaya, 2023)
Learning Arabic speaking skills is very important in learning a foreign language because language is a communication tool. However, students experience difficulties in developing Arabic speaking skills. This is due to the lack of student motivation and practice in speaking Arabic. So a project-based learning strategy is used to overcome this problem. This learning process can make students more active and creative in learning to speak Arabic. This research was conducted to describe project-based learning strategies in speaking skills in the Arabic language learning process for class X MAN Batu City students. This research method uses descriptive qualitative, namely describing the data obtained. The data sources in this research are teachers and students of class X MAN Batu City. The data analysis technique used in this research describes the results of observations, interviews, student product results and student responses to the learning process. The findings of this research are that the project-based learning process for class X students' speaking skills at MAN Batu City can stimulate motivation and enthusiasm for learning. In conclusion, project-based learning aims to solve problems and teach students to think critically in the product completion process. The steps that teachers can use in the project-based learning process are: 1) determine the basic problem, 2) create a project plan, 3) work on the project, 4) present the product results, 5) assess, and 6) evaluate. The product results are used as a student portfolio to determine their learning progress. This learning strategy can be practiced by teachers in the process of learning Arabic or other foreign languages.